Clinical features and follow‐up of pediatric patients hospitalized for COVID‐19. Issue 7 (14th April 2021) - Tang, Feng; Luo, Wanjun; Wang, Xiaowen; Li, Hui; Mei, Hong; Shao, Jianbo; Song, Qifa
Abstract: Objective: This report summarizes the clinical features and 1‐month follow‐up observations for pediatric patients who were hospitalized with coronavirus disease 2019 (COVID‐19) in Wuhan Women and Children's Hospital. Methods: The 1‐month follow‐up data included clinical manifestations and results from serum severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) IgG and IgM tests, reverse‐transcription polymerase chain reaction (RT‐PCR) for SARS‐CoV‐2, lung computed tomography (CT) scans, and laboratory tests. Results: Between January 20 and March 15, 2020, 127 patients aged 0–15 years were hospitalized for COVID‐19 treatment, including 3 severe cases and 124 mild or moderate cases. The main therapies included inhalation of aerosolized interferon‐α (122/127) and additional antiviral drugs (28/127). Among the 81 patients who had pneumonia at admission, 35 with right lobe pneumonia had the longest hospital stay (mean 14.5 ± 7 days); 17 with left lobe pneumonia had the highest creatine kinase (154 ± 106 U/L) and creatine kinase myocardial band (CK‐MB, 43 ± 48 U/L) levels; and 29 with bilateral pneumonia had the highest white blood cell counts (8.3 ± 4 × 10 9 /L). Among the 46 patients who were successfully followed up 1 month after discharge, two notable findings were right lobe pneumonia in 22% (95% confidence interval [CI]: 11%–37%) of patients and persistently elevated serum creatine kinase and CK‐MB levels. The median duration of elevated CK‐MB was 45 days. The mean concentrations of serum SARS‐CoV‐2 IgG and IgM in 41 patients were 8.0 ± 7.5 and 98 ± 40 ng/ml, respectively. At follow‐up, four patients retested positive for SARS‐CoV‐2. Conclusions: The involvement of different lung lobes in patients with COVID‐19 was associated with variations in the persistence of pneumonia and elevation of CK‐MB levels and body temperature.